What Makes for a Better Life? The Determinants of Subjective Well-Being in OECD Countries - Evidence from the Gallup World Poll - Boarini, Romina (OECD Statistics Working Papers, 2012)
This paper uses data from the Gallup World Poll to explore the determinants of subjective well-being. The paper builds on the existing literature on the determinants of subjective well-being in three areas. First, the paper systematically examines the drivers of measures of affect as well as the determinants of life satisfaction that are more prevalent in the existing literature. Overall, items relating to health status, personal security, and freedom to choose what to do with one's life appear to have a larger impact on affect balance when compared to life satisfaction, while economic factors such as income and unemployment have a more limited impact. The second part of the paper considers the degree to which there is heterogeneity in the weights assigned by different population sub-groups to the different determinants of subjective well-being. Relatively small differences are found between men and women, but priorities change significantly over the life course. Finally, the paper uses OECD data on the labour market and health policy regimes in different countries to test for the impact of these policy regimes on subjective well-being. Significant results are found for the replacement rate for unemployment assistance, employment protection legislation, and the extent of health co-payments. Although these results are tentative, they suggest that looking for the impact of policy changes on subjective well-being in large cross-country datasets is a promising area for research